All the miracles of the Bible the supernatural in Scripture, its scope and significance - Lockyer, Herbert, 1886- (Grand Rapids, MI Zondervan, 1961)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Miracles in the Bible